Bioprocessing of “Hair Waste” by Paecilomyces lilacinus as a Source of a Bleach-Stable, Alkaline, and Thermostable Keratinase with Potential Application as a Laundry Detergent Additive: Characterization and Wash Performance Analysis - Cavello, Ivana Alejandra (2012)
Paecilomyces lilacinus (Thom) Samson LPS 876, a locally isolated fungal strain, was grown on minimal mineral medium containing “hair waste,” a residue from the hair-saving unhairing process, and produced a protease with keratinolytic activity. This enzyme was biochemically characterized. The optimum reaction conditions, determined with a response surface methodology, were 60°C and pH 6.0. It was remarkably stable in a wide range of pHs and temperatures. Addition of Ca2+, Mg2+, or sorbitol was found to be effective in increasing thermal stability of the protease. PMSF and Hg2+ inhibited the proteolytic activity indicating the presence of a thiol-dependent serine protease. It showed high stability toward surfactants, bleaching agents, and solvents. It was also compatible with commercial detergents (7 mg/mL) such as Ariel, Skip, Drive, and Ace, retaining more than 70% of its proteolytic activity in all detergents after 1 h of incubation at 40°C. Wash performance analysis revealed that this protease could effectively remove blood stains. From these properties, this enzyme may be considered as a potential candidate for future use in biotechnological processes, as well as in the formulation of laundry detergents.